Public Health Practitioner Expert Opinion for Recommending Revisions to a Community Nutrition MPH Curriculum - Judy E Perkin; Catherine Christie; Desiree Hayes (University of North Florida, 2005)
Soliciting practitioner input into the planning or revision of Master of Public Health programs is desirable to ensure that students are adequately prepared for public health practice. Members of the American Dietetic Association Public Health/Community Nutrition Dietetic Practice Group (ADA-PH/CNDPG) were surveyed regarding the structure of, as well as the knowledge and skills desirable for, inclusion in a Master of Public Health community nutrition program. A total of 998 surveys were mailed in June 2001 with a return rate of 34%. Approximately 73% of respondents indicated public health employment. The average response regarding optimal time for full-time degree completion was 21.5 months. Almost 60% indicated that a practice component should be required. Important topics to be included in a degree core were assessed as: (1) community assessment; (2) program planning; and (3) health promotion/disease prevention. Nutrition content areas ranked highest were: (1) nutritional epidemiology; (2) nutrition and chronic disease; and (3) nutritional assessment. Core areas ranked highest to be separate courses were: (1) epidemiology; (2) community assessment; and (3) health promotion/ disease prevention. Nutrition areas ranked highest to be separate courses were: (1) nutritional epidemiology; (2) nutrition education; and (3) nutrition and chronic disease prevention. Survey results will help educators better prepare students for practice.